2020
DOI: 10.1088/1757-899x/986/1/012034
|View full text |Cite
|
Sign up to set email alerts
|

Methodology of constructing highly adequate models of additively manufactured materials

Abstract: In the this paper there is a description of the methodology of constructing highly adequate models of materials which are produced additively. The paper consists of introduction to the problem, demonstration of each step of the methodology and conclusions about the method and its applicability. The developed approach is presented on the two additively manufactured metal alloys. The modeling process is based on the orthotropic model of elasto-plastic material behavior. The list of material properties to be foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…However, the degree of this influence was not as large as in other studies. For example, in [29], an analysis was performed for the same material as was considered in this study, and also for aluminium alloy AlSi10Mg. A comparison of these two materials in terms of microstructure and orthotropic properties revealed that aluminium exhibited more pronounced orthotropic properties than titanium.…”
Section: Discussionmentioning
confidence: 99%
“…However, the degree of this influence was not as large as in other studies. For example, in [29], an analysis was performed for the same material as was considered in this study, and also for aluminium alloy AlSi10Mg. A comparison of these two materials in terms of microstructure and orthotropic properties revealed that aluminium exhibited more pronounced orthotropic properties than titanium.…”
Section: Discussionmentioning
confidence: 99%
“…For the implementation of such benches, first of all, sufficiently accurate mathematical models are needed [1][2][3]. These models should reflect the physical processes occurring during the creation of the testing environment and their computer implementations.…”
Section: Virtual Benches For Testing Vehicle Passive Safetymentioning
confidence: 99%